Scientific opinion on the presence of DNA in the feed additives consisting of concentrated liquid l‐lysine, l‐lysine monohydrochloride and concentrated liquid l‐lysine monohydrochloride produced by Escherichia coli NITE BP‐02917 for all animal species (METEX NOOVISTAGO) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on concentrated liquid l‐lysine, l‐lysine monohydrochloride and concentrated liquid l‐lysine monohydrochloride produced by a genetically modified strain of Escherichia coli (NITE BP‐02917) as nutritional and as sensory (flavouring compound) feed additives for all animal species. In 2022, the FEEDAP Panel issued an opinion on the safety and efficacy of these products. In that assessment, the FEEDAP Panel could not exclude the potential presence of recombinant DNA derived from the genetically modified production organism in the products. The applicant provided supplementary data to exclude the presence of recombinant DNA derived from the production organism in the final products. Based on the new data provided, the FEEDAP Panel concluded that no DNA of the production strain E. coli NITE BP‐02917 was detected in concentrated liquid l‐lysine, l‐lysine monohydrochloride and concentrated liquid l‐lysine monohydrochloride.